Reducing psychological distress in immigrants living in Spain through the practice of flow meditation (European Journal of Education and Psychology, 2009)
This study analyzes the effects of a meditation program on levels of psychological distress in a group of immigrants of different nationalities who live in Spain. An experimental group received the meditation intervention and a control group did not. A quasi-experimental design was used, comparing the groups with pre- and post-test measurements. Levels of psychological distress in the two groups were assessed using Derogatis’ SCL-90-R questionnaire. Statistical analyses showed significant differences between the experimental and control groups on all dimensions and general measures assessed through the SCL-90-R questionnaire, with participants in the meditation program achieving significant reductions in these dimensions and measures as compared to the control group. We therefore consider that meditation techniques can be a suitable therapeutic recourse in the care and prevention of psychological problems which the immigrant population is at risk for.Key words: Meditation, mindfulness, psychological distress, immigrants, culture clash.